2015
DOI: 10.1245/s10434-015-4997-y
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Total Mesorectal Excision Versus Laparoscopic Surgery for Rectal Cancer Receiving Neoadjuvant Chemoradiation: A Matched Case–Control Study

Abstract: This matched case-control study demonstrated that TaTME is safe and feasible. Compared with LapTME, TaTME not only achieves identical circumferential margin status without compromising other operative and quality parameters but also benefits patients by achieving a longer distal margin. Thus, TaTME has the potential to become an option in managing irradiated rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 24 publications
5
114
2
1
Order By: Relevance
“…Nevertheless, due to its complexity, the usage of different minimally invasive techniques in taTME is associated with a significant rate of intraoperative rectal, vaginal, or bladder injury during the learning curve, mainly due to the anatomical landmarks which are different from those during standard laTME from above. However, beyond the learning curve, the rate of intraoperative complications decreases [26,27,28]. Postoperative outcomes and oncological results of taTME and laTME were reported by several retrospective and comparative studies to be similar.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, due to its complexity, the usage of different minimally invasive techniques in taTME is associated with a significant rate of intraoperative rectal, vaginal, or bladder injury during the learning curve, mainly due to the anatomical landmarks which are different from those during standard laTME from above. However, beyond the learning curve, the rate of intraoperative complications decreases [26,27,28]. Postoperative outcomes and oncological results of taTME and laTME were reported by several retrospective and comparative studies to be similar.…”
Section: Discussionmentioning
confidence: 99%
“…In one study (47), the extent of the distal resection margins was reported as >1cm in 78% after LapTME, and in 77% after TATME. In two studies (44,45), the extent of free distal resection margins was significantly longer after TATME.…”
Section: Minimally Invasive Therapy and Allied Technologiesmentioning
confidence: 94%
“…These patients were enrolled in 33 publications according to three types of clinical studies: case reports (17,(19)(20)(21)(22), clinical case series (retrospective and prospective) (11,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)42), and comparative studies (43)(44)(45)(46)(47)(48)(49).…”
Section: Demographics Of Patients Included In Case Reports and Clinicmentioning
confidence: 99%
See 1 more Smart Citation
“…Three recently published non-randomized comparative studies presented conclusions similar to those of our institutional study. While none of these three studies showed any oncological superiority, they did report substantial advantages in short-term outcomes with trans-anal endoscopic proctectomy compared with standard laparoscopy [2729]. Finally, we performed a single-institution case-controlled comparative study ( n  = 72) [30] and found that ETAP could make the procedure easier and improve short-term outcomes without impairing the oncological quality or outcome.…”
Section: Introductionmentioning
confidence: 99%